2011
DOI: 10.1177/0194599811424120
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Landline Telephone Performance Outcomes among Telephone‐Using Cochlear Implant Recipients

Abstract: Many cochlear implant recipients achieve good objective telephone speech perception performance, indicating that they should be effective telephone users, especially when using mobile telephones and among younger implant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Children with profound congenital hearing loss have been able to develop excellent speech and language and the majority attend mainstream schools [Venail et al, 2010]. The majority of established CI users are now able to use the telephone [Tan et al, 2012]. Refinements to hardware and surgical technique have continued over the years in many ways, both contributing to improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Children with profound congenital hearing loss have been able to develop excellent speech and language and the majority attend mainstream schools [Venail et al, 2010]. The majority of established CI users are now able to use the telephone [Tan et al, 2012]. Refinements to hardware and surgical technique have continued over the years in many ways, both contributing to improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cochlear implants (CIs) often show worse speech recognition on the telephone compared to everyday communication . Currently, up to 35% are unable to use the telephone at all and this has been identified as a major source of reduced quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most of the authors have focused on the phone perception ability of CI recipients using phone signal simulations [8,16]. Surprisingly, only very few studies have been based on real telephone transmission [14]. In addition, these studies did not provide details about the objective testing methods; older articles also did not reflect the current state of the art for CIs.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the technological revolution in this area that has occurred in recent years with the advent of the latest generations of smartphones, characterized by unprecedented functionality and listening comfort. A recent work by Tan et al [14] demonstrated a considerably higher benefit from mobile phone use rather than from traditional phones, with a mean speech recognition score statistically higher with the former (57% vs 84.3%). In addition, the authors stressed the importance of the mobile phone model for the quality and quantity of understanding.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation